Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given a (continuous) bivariate random vector $(X,Y)$ with a probability density:

$$f_{XY}(x,y)=\left\{ \begin{array}{l}\tfrac{1}{y}e^{-(y+\tfrac{x}{y})} & \text{if }x>0 \text{ and } y>0 \\ 0 & \text{otherwise}\end{array} \right.$$

Find the marginal density $f_X(x)$ and $f_Y(y)$ and show whether $X$ and $Y$ are stochastically independent.

In my attempt, I tried to calculate the marginal densities as follows:

$$\begin{align*}f_Y(y) &= \int_{-\infty}^{\infty}f_{XY}(x,y)\mathrm{d}x \\ &= \int_{0}^{\infty}\tfrac{1}{y}e^{-(y+\tfrac{x}{y})}\mathrm{d}x\\ &= -\lim_{N \to \infty} \left[ e^{-(y+\tfrac{x}{y})} \right]_0^N \\ &= -\lim_{N \to \infty} (e^{-(y+\tfrac{N}{y})}-e^{-(y+\tfrac{0}{y})})\\ &= e^{-y}-0 = \frac{1}{e^y} \end{align*}$$ $\\$ $$\begin{align*}f_X(x) &= \int_{-\infty}^{\infty}f_{XY}(x,y)\mathrm{d}y \\ &= \int_{0}^{\infty}\tfrac{1}{y}e^{-(y+\tfrac{x}{y})}\mathrm{d}y\\ \end{align*}$$

But I get stuck at solving this last integrals. How should this be solved?

Thanks in advance.

share|cite|improve this question

The expression for $f_X(x)$ is not elementary. In fact, the integral is a defining integral for the Macdonald function: $$ f_X(x) = \int_0^\infty \exp\left(-y - \frac{x}{y}\right)\frac{\mathrm{d}y}{y} = \left.\left( \underbrace{\left(\frac{z}{2}\right)^\nu \int_0^\infty \exp\left(-t-\frac{z^2}{4t} \right) \frac{\mathrm{d}t}{t^{\nu+1}}}_{2 K_\nu\left(z\right)}\right)\right|_{\nu=0,z=2 \sqrt{x}} = 2 K_0\left(2 \sqrt{x}\right) $$ where $x$ was assumed positive. Anyhow, you readily conclude that $f_{X,Y}(x,y) \not= f_X(x) f_Y(y)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.